Plexitis as a predictive factor of early postoperative clinical recurrence in Crohn's disease. Issue 9 (21st July 2009) - Sokol, H; Polin, V; Lavergne-Slove, A; Panis, Y; Treton, X; Dray, X; Bouhnik, Y; Valleur, P; Marteau, P
Abstract : Background and aims: A previous study suggested that the presence of myenteric plexitis in the proximal resection margins could be predictive of early endoscopic recurrence after ileocolonic or ileal resection for Crohn's disease (CD). The aim of the present study was to assess the predictive value of plexitis for early clinical CD recurrence. Methods: All consecutive patients with ileocolonic or ileal resection for active CD in Lariboisière Hospital (Paris) between 1995 and 2006 were included. Clinical, surgical, histological and follow-up data were extracted from medical charts. Early clinical recurrence was defined as the reappearance of CD clinical manifestations requiring a specific treatment within 2 years postsurgery. The proximal resection margin was analysed using haematein eosin saffron (HES) staining and immunochemistry targeting mastocytes (anti-CD117 antibody) and lymphocytes (anti-CD3 antibody). Eosinophils were detected by HES staining. Ten cases of ileocolonic resections for caecal carcinoma served as controls. Results: Data were available from 171 postoperative follow-up periods in 164 patients with CD. Early clinical recurrence of CD occurred in 28.1%. In multivariate analysis, factors associated with postoperative recurrence were active smoking (hazard ratio (HR) = 1.94; 95% CI 1.06 to 3.60; p = 0.033), submucosal plexitis with ⩾3 mastocytes (HR = 1.87; 95% CI 1.00 to 3.46; p = 0.048) and a disease-free resection margin <5 cm (HR = 0.52; 95% CI 0.27 to 1.02; p = 0.059). Conclusions: Submucosal plexitis is associated with early clinical recurrence and could be taken into account in studies searching for new treatment strategies in the immediate postoperative period.